ODPOWIEDZIALNOŚĆ III RP ZA SZKODY WYRZĄDZONE PRZEZ WŁADZE PUBLICZNE W LATACH 1944-1989 - Łączkowski, Wojciech (Wydział Prawa i Administracji UAM, 2012)
Zgodnie z zasadą, że za szkodę odpowiada jej sprawca lub następca prawny, III RP nie powinna ponosić odpowiedzialności za krzywdy wyrządzone z powodów ustrojowo-politycznych przez władze publiczne funkcjonujące na obszarze Polski w latach 1944-1989. Władze te w zasadniczych sprawach były niesamodzielne, będąc jedynie wykonawcami decyzji kierownictwa ZSRR – dotyczy to również szkód, o których mowa w artykule. Skoro jednak jest mało prawdopodobne, aby Federacja Rosyjska (następca prawny ZSRR) uznała jakiekolwiek roszczenia odszkodowawcze, należy poszukiwać innych rozwiązań. Możliwa, a nawet wskazana, jest pomoc poszkodowanym, ale nie na gruncie prawa do odszkodowania, lecz w oparciu o przesłanki etyczne i z uwzględnieniem możliwości finansowych Państwa. Jedynie w sytuacjach utrzymujących stan bezpodstawnego wzbogacenia dzisiejszych władz publicznych lub osób, które wzbogaciły się w złej wierze kosztem pokrzywdzonych, należałoby uwzględniać roszczenia prawowitych właścicieli, korzystając z rozwiązań podobnych do tych, które określone są w Kodeksie cywilnym. Rozważania zawarte w artykule odnoszą się jedynie do stosunków wewnętrznych, w stosunkach międzynarodowych bowiem brak suwerenności Polski w tamtym okresie nie może już wywoływać żadnych skutków praktycznych. Ponadto artykuł nie dotyczy odszkodowań należnych Kościołom i związkom wyznaniowym. Jest to problematyka, którą należy połączyć z szerszą sprawą finansowania Kościołów.

*Pursuant to the principle that the perpetrator or his legal successor is liable for the damage caused, The Third Republic of Poland shall not be held liable for the damage resulting from the actions taken by public authorities that functioned in the territory of Poland in the political regime of 1944-1989. Those authorities, in all fundamental matters, did not act independently, but merely implemented the decisions, also the damaging ones, that had been made by the Soviet Union. And yet, it is highly unlikely that the Russian Federation (the legal successor of the USSR) will ever recognise any claims for damages or compensation for the damage caused. Consequently, other possibilities must be considered. What seems possible and recommended is assistance offered to the harmed citizens, although such assistance is not provided by the law but is rooted in the principles of ethic and depends on the financial capability of the State involved. Solutions similar to those provided in the Civil Code should be resorted to only in situations where the state of unjust enrichment continues to be enjoyed by today’s public authorities, or individuals who acquired unlawful gains in bad faith, at the cost of others. The deliberations presented in the paper apply to the internal situation in the state only since the fact that in the analysed period Poland was not a sovereign state will not, any longer, have any practical consequences for international relations. Further, the subject matter of this paper does not concern compensation due to the Church and religious denominations, which is part of a much more broadly understood area pertaining to the financing of Churches.
LIABILITY OF THE THIRD REPUBLIC OF POLAND FOR THE DAMAGE CAUSED IN THE PERIOD 1944-1989
Keywords: PRL; prawo do odszkodowania; III RP; przesłanki etyczne; Polish People's Republic; Third Republic of Poland; claim for damages; principles of ethic